Mast cell gastritis: Children complaining of chronic abdominal pain with histologically normal gastric mucosal biopsies except for increase in mast cells, proposing a new entity - Pourpak Zahra; Farahmand Fatemeh; Mahjoub Fatemeh E; Asefi Hoda; Amini Zahra (BMC, 2009)
Abstract Background Mast cells reside within the connective tissue of a variety of tissues and all vascularized organs. Since 1996, few studies have been performed on mast cell density in gastrointestinal biopsies, mainly in adult age group. We recently studied mast cell density in pediatric age group on rather larger number of cases in a referral children hospital. Mast cell density was 12.6 ± 0.87 in 0.25 mm2 (range: 0-81) in our study. Since we frequently encounter cases with rather normal gastric biopsies with no H.pylori, which mainly complain of chronic abdominal pain, we gathered those cases with mast cell density more than 30/0.25 mm2. from 895 gastric biopsies and wanted to study their clinical and endoscopic findings and propose a new entity. Methods Between April 2005 and May 2008, 895 children (< 14 years old), with gastrointestinal complaints who underwent endoscopy were selected and antral biopsies were obtained for histological examination. Among these children, those who had normal or erythematous (but not nodular or ulcerative) gastric mucosa on endoscopic view, plus pathologic report of normal mucosa or mild gastritis in addition to mast cell count more than 30/25 mm2, were chosen and a questionnaire was filled for each patient including clinical, endoscopic and pathologic findings. The statistical analysis was performed using SPSS, version 13 (SPSS Inc., Chicago, IL, USA). Results Over a 3 year period of study, of 895 selected children, 86 patients fulfilled the entrance criteria. The major complaint of patients was recurrent abdominal pain. The mean mast cell density was 45.59 ± 13.81 in 0.25 mm2 (range: 30-93). Among our cases, about 67.4% (n = 58) had 30 to 49, 23.3% (n = 20) had 50 to 69, 8.1% (n = 7) had 70 to 89 and 1.2% (n = 1) had 93 mast cells/0.25 mm2 in their specimens Discussion In 29% of our cases, neither endoscopic nor pathologic change was detected and only increase in mast cell number was reported and in others endoscopic and histopathological findings were negligible except increase in mast cells. In updated Sydney system (classification and grading of gastritis), no term is introduced which is in concordance with this group but we think that increased density of mast cells in these cases should not be overlooked and it may contribute to clinical manifestations in some way. We hope that further studies will direct us to institute therapeutic measurements in this regard.